Handbook on the Wisdom books and Psalms job, psalms, proverbs, ecclesiastes, song of songs - Estes, Daniel J. 1953- (Grand Rapids, Mich. Baker Acad., 2005)
Job -- Psalms -- Proverbs -- Ecclesiastes -- Song of songs
Job -- Psalms -- Proverbs -- Ecclesiastes -- Song of songs
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Wisdom Literature -- Criticism, interpretation, etc